2021
DOI: 10.3126/ijosh.v11i2.37259
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among healthcare professionals in Nepal: An analytical study

Abstract: Introduction: The greater risk of burnout among healthcare professionals is likely to develop an adverse effect on their personal life and the patients’ care. The main aim of this study was to assess the levels of burnout experienced by healthcare workers. Methods: A cross-sectional study was conducted from November 2020 to March 2021 among healthcare professionals working in different institutions. A convenient sampling technique was applied. An online questionnaire was developed using Google Forms. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The findings of this study revealed that nurses have suffered moderate to high levels of compassion fatigue (77.0% -3.5%) and burnout (76.5% -0.9%) during the COVID-19 health crisis. These findings are almost similar with the study conducted in Nepal, which reported moderate to high level of burnout among nurses (92.2%-3.9%) and secondary traumatic stress relationship was found between burnout and compassion fatigue (r= .522: p=0.000) which is consistent with the findings of studies done in Nepal 12 and Spain. 17 Similar result is reported in meta-analysis in which compassion fatigue and burnout were positively correlated (r =0.59) whereas compassion satisfaction was negatively correlated with burnout (r = -0.446) and compassion fatigue (r= -0.226).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study revealed that nurses have suffered moderate to high levels of compassion fatigue (77.0% -3.5%) and burnout (76.5% -0.9%) during the COVID-19 health crisis. These findings are almost similar with the study conducted in Nepal, which reported moderate to high level of burnout among nurses (92.2%-3.9%) and secondary traumatic stress relationship was found between burnout and compassion fatigue (r= .522: p=0.000) which is consistent with the findings of studies done in Nepal 12 and Spain. 17 Similar result is reported in meta-analysis in which compassion fatigue and burnout were positively correlated (r =0.59) whereas compassion satisfaction was negatively correlated with burnout (r = -0.446) and compassion fatigue (r= -0.226).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent findings were reported in the study conducted in Nepal, where 88.2% of nurses reported moderate level of compassion satisfaction. 12 However, Franza et al (2020) showed 45.83% of nurse had moderate to high level of compassion satisfaction in the time of covid-19 outbreak. 7 Likewise, Borges (2019) found high level of compassion satisfaction among 51% of the nurses in Portugal.…”
Section: Outmentioning
confidence: 99%
See 2 more Smart Citations
“…The same findings have been noted in multiple other studies and may be associated with physiological age-related changes or with added responsibility with increased age . 28,32,34 The mean scores for both the disengagement and exhaustion domains were significantly higher in female gender. These findings are consistent with available literature.…”
Section: Discussionmentioning
confidence: 96%